Internally Compensated LDO Regulators for Modern System-on-Chip Design - Hinojo, José María (Springer International Publishing, 2018)
This book presents a thorough state-of-the-art review for internally compensated Low Dropout Regulators (IC-LDO). It serves as a useful guide for circuit designers. The advantages and disadvantages of each cell proposed are highlighted. The authors describe an alternative to the classical topology; the Flipped Voltage Follower (FVF), which has been recently applied in the design of internally compensated LDOs to enhance their performances. This book provides novel circuits enhancing those parameters of LDO related with frequency behavior and power consumption. These solutions, as well as their appropriate design methodology, are properly described within the text.